2015
DOI: 10.1042/bj20150068
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the structures and ligand-binding sites of nematode fatty acid and retinol-binding proteins revealed by Na-FAR-1 from Necator americanus

Abstract: Necator americanus fatty acid and retinol-binding protein-1 (Na-FAR-1) is an abundantly expressed FAR from a parasitic hookworm. The present work describes its tissue distribution, structure and ligand-binding characteristics and shows that Na-FAR-1 expands to transport multiple FA molecules in its internal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 71 publications
5
45
0
Order By: Relevance
“…Predictions of the 3D structure of Mj‐FAR‐1 also reveal new features for this protein when compared to the 3D crystal structure of Ce‐FAR‐7, such as a bigger electrostatically charged P2 pocket that could accommodate larger isoprenoid chains of retinol and other compounds with charged characteristics (Iberkleid et al ., ). These differences are in agreement with the 3D structure of the Na‐FAR‐1 of N. americanus determined by nuclear magnetic resonance and X‐ray crystallography, probably reflecting differences in their ligand selectivity (Rey‐Burusco et al ., ). One route to determine the function of FAR‐1 of M. javanica has been recently performed by overexpressing Mj‐far‐1 in stable hairy root lines of tomato, and studying the consequential gene expression changes by transcriptome data analyses (Iberkleid et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Predictions of the 3D structure of Mj‐FAR‐1 also reveal new features for this protein when compared to the 3D crystal structure of Ce‐FAR‐7, such as a bigger electrostatically charged P2 pocket that could accommodate larger isoprenoid chains of retinol and other compounds with charged characteristics (Iberkleid et al ., ). These differences are in agreement with the 3D structure of the Na‐FAR‐1 of N. americanus determined by nuclear magnetic resonance and X‐ray crystallography, probably reflecting differences in their ligand selectivity (Rey‐Burusco et al ., ). One route to determine the function of FAR‐1 of M. javanica has been recently performed by overexpressing Mj‐far‐1 in stable hairy root lines of tomato, and studying the consequential gene expression changes by transcriptome data analyses (Iberkleid et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Nematode lipid-binding proteins play key roles in the transport of fatty acids and retinols, which are ultimately consumed for important metabolic and developmental processes of the nematode, such as embryogenesis, glycoprotein synthesis, growth and cellular differentiation (McDermott et al, 1999;Kennedy, 2000). Fluorescencebased ligand binding assays have shown that recombinant FARs of parasitic nematode species possess a strong binding activity to fatty acids and retinol (Rey-Burusco et al, 2015;Zhang et al, 2015;Qiao et al, 2016), and recent studies suggest that FARs are also capable of binding to a wide range of lipidic compounds such as diacylglycerol and phospholipids (Franchini et al, 2015). In animal-parasitic nematodes, FARs have been found within the excretory/secretory secretome, together with an extensive series of proteins that can interact with a range of activities of the nematode, to facilitate invasion and contribute to immune modulation of the host (Garofalo et al, 2002;Kennedy et al, 2013).…”
Section: Figurementioning
confidence: 99%
“…These data show that Ace-FAR-1 might help fatty acid uptake for cuticle integrity, egg generation, and embryo development [144]. On the contrary, Na-FAR-1 was localized in the male copulatory bursa and the adult worm intestine, indicating their roles in male reproduction and nutrient uptake [146]. FAR might promote the parasite infectivity and lower the intestinal mucosal IgA levels through decreasing the retinol amount required for repairing the intestinal injuries and upregulating Th2 cytokine response, respectively [143].…”
Section: Fatty-acid and Retinol-binding Proteinsmentioning
confidence: 85%
“…The FAR-1 and FAR-2 proteins have six other isoforms described in C. elegans, which are localized in the cell membrane and are related to cell signaling and the immune response. Previous studies showed the bound capacity of these proteins in anthelmintics, such as albendazole, levamisole, abamectin, and praziquantel (REY-BURUSCO et al, 2015;QIAO et al, 2016). Thus, it is possible to suggest that FAR-1 and FAR-2 promote ivermectin resistance mechanisms by triggering biological signaling in addition to their possible role in recruiting fatty acids to contribute to the maintenance of energetic balance during the stress induced by the anthelmintic agent.…”
Section: Discussionmentioning
confidence: 99%